Electron beam irradiation effects on variable starch content flat-type rice noodle physicochemical and microbial properties - M.D, Ahmad Zainuri; W. I., Wan Zunairah; A. R., Farah Nadiah; J., Akmal; M. A.R., Nor-Khaizura; M., Nor Afizah; M. R., Ismail-Fitry; S., Radhiah; Z. A., Nur Hanani (Akademi Sains Malaysia, 2026)
Flat rice noodles (FRN) or kuetiau made from rice and starch are popular in Malaysia. FRN is a non-gluten noodle and requires gelatinisation of starch during processing. FRN is considered a highly perishable food due to its high moisture content, which is susceptible to microbial deterioration. Electron beam irradiation was performed on FRN's physical, chemical, and microbiological properties. FRN was prepared with 90% rice flour; the remaining 10% was either tapioca, potato, or sago. The noodle was then irradiated at 0, 3, 6, and 9 kGy by electron beam (EB). EB irradiation significantly increased the firmness, breaking length, and cooking loss, whereas the cooking yield and yellowness (b*) of the FRN were significantly decreased. However, all irradiation doses did not affect the pH, water activity, moisture content, lightness (L*), and greenness (a*). The total plate count (TPC) of the FRN was determined on days 0, 2, 4, 6, 8, and 10. The results showed that the irradiation dose at 9 kGy was the most effective as it reduced the microbial count until day 10. Thus, the pH, moisture content, water activity, lightness, and greenness of FRN were not changed by EB irradiation, but the textural and cooking qualities were considerably altered.